Representation of Family Communication in the Film “Bila Esok Ibu Tiada” Through Fiske’s Lens - Idiani, Intan; Ammelia, Euis; Intan, Dian Mustika (Journal Analytica Islamica, 2025)
This study analyzes the representation of family communication in the film "Bila Esok Ibu Tiada" using John Fiske's semiotic framework. The film tells the story of a mother, Rahmi,'s struggle to maintain the integrity of her household after her husband's departure. A descriptive qualitative approach was used, with data collection techniques through non-participant observation of the film. Data analysis was conducted at Fiske's three levels of meaning: Reality Level, Representation Level, and Ideology Level, by identifying visual, audio, and cinematography technical codes. The results of the study show that the film effectively displays the breakdown in communication and the mother's loneliness through behavior, gestures, dialogue, and environment. The conflict peaks when the children realize their mother's absence and find the results of the hospital examination, triggering profound emotional changes. Representation codes, such as the use ofshaky camand changes in rhythmeditingfrom dynamic to slow, as well as melancholic music and gloomy lighting, strengthen the emotional impact and meaning. At the ideological level, the film highlights the mother's infinite sacrifice and the tension between modern individualism and the traditional family collectivism value. The Kintsugi philosophy becomes a metaphor for reconciliation, encouraging children's awareness of the importance of family ties. In conclusion, the film successfully constructs a complex meaning about the importance of appreciating the presence of parents and repairing broken family relationships through layered semiotic elements.